2023
DOI: 10.1371/journal.pbio.3001956
|View full text |Cite
|
Sign up to set email alerts
|

Combined modelling of mRNA decay dynamics and single-molecule imaging in the Drosophila embryo uncovers a role for P-bodies in 5′ to 3′ degradation

Abstract: Regulation of mRNA degradation is critical for a diverse array of cellular processes and developmental cell fate decisions. Many methods for determining mRNA half-lives rely on transcriptional inhibition or metabolic labelling. Here, we use a non-invasive method for estimating half-lives for hundreds of mRNAs in the early Drosophila embryo. This approach uses the intronic and exonic reads from a total RNA-seq time series and Gaussian process regression to model the dynamics of premature and mature mRNAs. We sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 85 publications
1
15
0
Order By: Relevance
“…Previous studies in cell culture systems found that median half-life is roughly proportional to cell cycle length (Vejnar et al 2019). A study of decay in early Drosophila melanogaster embryos (nc11 through cephalic furrow formation), which have comparable cell cycle lengths (~10-180 minutes) to those in the C. elegans embryo (Foe 1989;Bao et al 2008), observed a similar range of half-lives to ours for ~260 zygotic transcripts (Beadle et al 2023). In older fly embryos (stage 12 to 15), which have longer cell cycles, the median half-life was longer at 73 minutes (Burow et al 2015).…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies in cell culture systems found that median half-life is roughly proportional to cell cycle length (Vejnar et al 2019). A study of decay in early Drosophila melanogaster embryos (nc11 through cephalic furrow formation), which have comparable cell cycle lengths (~10-180 minutes) to those in the C. elegans embryo (Foe 1989;Bao et al 2008), observed a similar range of half-lives to ours for ~260 zygotic transcripts (Beadle et al 2023). In older fly embryos (stage 12 to 15), which have longer cell cycles, the median half-life was longer at 73 minutes (Burow et al 2015).…”
Section: Discussionsupporting
confidence: 77%
“…As another layer of validation, we further explored their relative contributions to mRNA enrichment in P-bodies (Courel et al, 2019). P-bodies are membraneless granules for RNA storage and turnover (Beadle et al, 2023). We uncovered a positive correlation between TA dinucleotides and RNA P-body localization, especially for those occurring in 3’ UTRs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Later, in early embryogenesis, smaller and more dynamic P bodies reform [ 38 ], and this offers a unique avenue for the study of de novo condensate formation. Current work shows degradation intermediates for short-lived mRNAs accumulating in reformed P bodies during embryogenesis [ 54 ], and P body components Me31B, Decapping protein 1 (DCP1), Staufen (Stau), and Pacman (Pcm) accumulate with oskar ( osk ) mRNA, and this correlates with the degradation of the mRNA [ 55 ]. Additionally, biochemical data suggest that Me31B transitions from a translational repressor to a beacon for mRNA degradation after the maternal to zygotic transition (MZT) [ 56 ].…”
Section: Drosophila P Bodies Have Complex Compositions and Multiple F...mentioning
confidence: 99%
“…Unfortunately, there are only a few well-documented examples of RNAs that associate with P bodies in Drosophila [ 42 , 54 , 95 ], and more research is needed to fully understand the importance of RNA in P body biogenesis.…”
Section: In Vivo Exploration Of P Body Biogenesismentioning
confidence: 99%
See 1 more Smart Citation